INTERNALISASI NILAI-NILAI AKHLAK MURID DALAM PEMBELAJARAN AL-QUR’AN (TPA) DI KENTEN PERMAI - Siti Ayu Aisyah; Muhammad Win Afgani; Fajri Ismail (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
This research is entitled "Internalization of student moral values in learning the Qur'an (TPA) in Kenten Permai." qur'an. With the aim of this study to describe and analyze the general picture of student morals and the process of internalizing moral values in learning al-Qur'an education for students at the Al-Qur'an Education Park (TPA) in Kenten Permai. This research uses a qualitative descriptive research type. This research was conducted at the Al-Qur'an Education Park (TPA) in Kenten Permai, data collection techniques used observation, interviews and documentation. The validity of the data in this study uses the triangulation method and uses descriptive analysis to describe and explain the data obtained.